Listantia, Nora Sinergi Pembersihan Pantai Loang Baloq Kota Mataram - Listantia, Nora; Ningthias, Dyah Puspitasari; Rispawati, Dewi; Supriastuti, Eko; Sakaroni, Rubiyatna; Karoluslina; Hijriati, Sartika (Universitas Mataram, 2025)
This community service activity aims to increase environmental awareness and strengthen the synergy between university students, the community, and the local government in maintaining the cleanliness of Loang Baloq Beach, one of the religious tourism icons in Mataram City. The activity was carried out through community clean-up programs, environmental education, and sustainable waste management campaigns.The results of the program show an 85% increase in local community participation in the beach clean-up activities, as well as the emergence of community initiatives to continue conducting monthly clean-up routines. The synergy among students, universities, local communities, and the government has proven effective in creating positive behavioral changes toward coastal environmental conservation. The Loang Baloq beach clean-up synergy involved the National Disaster Management Agency (BNPB), the Indonesian Army (TNI AD), scout students, coastal communities, and university students.